Procalcitonin kinetics in the first 48 hours of ICU admission is associated with higher mortality in critically ill patients with community-acquired pneumonia in a setting of high HIV prevalence. (3rd September 2018) - Naidoo, K; De Vasconcellos, K; Skinner, DL
Abstract : Background: Severe community acquired pneumonia (CAP) commonly results in ICU admission and is associated with significant morbidity and mortality. Procalcitonin (PCT) may assist risk stratification and prediction of aetiology but is not well studied in critically ill patients with a high HIV prevalence. Methods: A retrospective observational study of patients admitted to ICU with a clinical diagnosis of CAP was undertaken. PCT on admission and at 48 hours was evaluated as a predictor of ICU outcome and pneumonia aetiology. Results: A total of 100 patients were included; 62% were HIV positive. Overall ICU mortality was 61%. PCT at admission and 48 hours was not associated with any outcome variables. A significant association was found between mortality and patients whose PCT levels increased or remained >10 ng/ml at 48 hours, compared with those that remained unchanged or decreased (67% vs. 41% p = 0.018). The commonest aetiology identified was Mycobacterium tuberculosis ( n = 18, 21.4%). Patients with admission PCT levels >10 ng/ml were more likely to have positive bacterial cultures (OR = 3.14; 95% CI 1.11–9.73). Conclusions: Increasing or persistently elevated PCT predicts a higher mortality in critically ill patients with CAP. This suggests PCT kinetics may be useful in risk stratifying patients with CAP at 48 hours. While positive bacterial cultures are more likely in patients with high admission PCT, this assay does not allow for decisions to be made on antimicrobial management and is of limited clinical utility in critically ill patients with a high HIV prevalence and CAP.